Smart car park detector / Wan Nurazwin Syazwani Rahimi & Nazrena Md Non - Rahimi, Wan Nurazwin Syazwani; Md Non, Nazrena (2015)
SMaCPaD Machine is a Smart Car Park Detector Machine that can display number parking on the LCD to user after push the button. These projects present about smart car park system. This project is to ease people to find their car in the shopping complex car parking as this project are design for them to just go straight to the chosen spotted parking. This project is design to make people to park the car easily by refer to the number parking shown at the LCD. Usually when we go to shopping complex for sure we want to park our car but it is difficult to find parking site and always have to round more longer because there is no empty parking site. When this happen, with not thinking twice people are always just park overlap with other parked car in order to enter the shopping complex. This situation can invite fights between car owners. So to prevent this from happening, this system is very useful and easier for them to park car by refer the given number parking that is shown on the ticket.